Revitalizing Hadrah Al-Banjari: Enhancing Spiritual Intelligence and Cultural Identity Among Indonesian Mosque Youth - Muhammad Edy Thoyib; Agwin Degaf; Zainur Rofiq; Miftahul Huda; Irham Irham (Jurnal Abdimas Mahakam, 2026)
Indonesian youth are experiencing rapid social and technological changes, impacting their spiritual and emotional development. This study explores the role of Hadrah Al-Banjari, a traditional Islamic art form, in enhancing spiritual intelligence among mosque youth. Positioned within the broader context of spiritual education, Hadrah Al-Banjari fosters spiritual awareness, emotional sensitivity, and cultural pride. Using qualitative data collected through interviews, focus group discussions, and observations, the study employed Participatory Action Research (PAR) to involve youth in understanding and improving their spiritual practices. The results indicate that Hadrah Al-Banjari serves as a valuable medium for spiritual education, deepening religious devotion and reinforcing Islamic values. The research highlights the need to revitalize traditional Islamic arts to support youth spiritual and cultural development. Future studies should explore the broader integration of these practices into community programs to enhance spiritual growth across diverse populations.